Pure embryonal carcinoma of testis presenting with extensive metastasis - Sunil Vitthalrao Jagtap,; Tasneem Vikramsingh Bisht,; Swati Sunil Jagtap,; Anil Huddedar, (Universiti Kebangsaan Malaysia, 2015)
Embryonal carcinoma is a type of non-seminomatous germ cell tumor. Pure embryonal carcinoma of testis occurs only in 3–4% cases. We present a case of 34-year-old man with aggressive clinical course. At the time of presentation, he had left testicular swelling along with supraclavicular mass with extensive metastasis to retroperitoneum, liver, and lung. On gross pathological examination, specimen showed tumor replacing entire testis with involvement of rete testis, epididymis, and spermatic cord. It is observed that many patients with a tumor composed predominantly of embryonal carcinoma have metastasis at the time of diagnosis. Embryonal carcinoma is an aggressive tumor due to its tendency to early hematogenous spread emphasizing its need for early detection and treatment. The estimation of serum tumor marker levels is not conclusive in these cases. We are presenting this case for its rarity, and advanced stage of disease with clinical and histomorphological features.